Practical enzymology - Bisswanger, Hans.; Wiley InterScience (Online service) (Weinheim : Wiley-Blackwell, 2011)
The second edition of the perfect companion for practical course work in enzymology. Now with an improved selection of enzymatic assays based on key metabolic reactions, this book provides the detailed background to the enzymatic reaction and the enzyme per se. Particular emphasis is placed on troubleshooting with the described methods, and, in addition, the new four-color layout throughout features detailed protocols highlighted for easy recognition. WWW.WILEY-VCH. DE/HOME/ENZYMOLOGY: A companion website provides animations for all figures together with supplementary material, for deepe.
General aspects of enzyme analysis -- Enzyme assays -- Binding measurements -- Enzymes in technical applications -- Appendix: list of enzymes according to EC numbers.
Online resource; title from PDF title page (EBSCO, viewed March 30, 2016).
Includes bibliographical references and index.
Keywords: Enzymology; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Enzymology; Electronic books